A pilot study of toxicological safety evaluation in acute and subacute (28-day) oral assessments of kenaf seed beverage in rats - Zaini, Nur Syamimi; Karim, Roselina; Abdull Razis, Ahmad Faizal; Hamid, Nur Fazila Saulol; Zawawi, Norhasnida (Elsevier, 2022)
Kenaf (Hibiscus cannabinus L.) seed is a non-conventional edible oilseed that can be valorized into various food products. There is a recent discovery of kenaf seed beverage (KSB) potential as a novel plant-based beverage. KSB had less crude protein than soybean (SB) but more carbohydrate, magnesium, and phosphorus contents. Levels of crude fat, phytates, oxalates, total saponins, and lipid peroxidability in KSB were lower than SB. Sugar content between KSB and SB were comparable, while antioxidant properties of KSB were superior. Ultra-high performance liquid chromatography-mass spectrometry (UHPLC-MS) analysis detected gluconic acid, citric acid, palmitic acid, oleic acid, and 13-hydroxyoctadecadienoic acid in both KSB and SB. Considering its novelty, acute and subacute oral toxicity assessments in male Sprague Dawley rats were conducted. The acute toxicity assessment was performed at a single dose of 9.2 ml/kg body weight of KSB. In the following subacute toxicity assessment, different groups of rats consumed different doses of KSB (3.1, 6.1, and 9.2 ml/kg body weight) daily for 28 days. Rats presented normal behavioral and physiological states in both toxicity studies. Growth, food and water intakes, organ weight, and hematological parameters were unaffected. No mortality was reported. Several alterations in serum biochemical parameters were within the normal range, and unassociated with histopathological changes. The oral lethal dose (LD50) and the no-observed-adverse-effect-level (NOAEL) of KSB in rats was greater than 9.2 ml/kg (=1533 mg/kg) body weight. Interestingly, KSB exhibited comparable effects with soybean beverage (SB) on high-density lipoprotein cholesterol and triglycerides which worth further research Follow-up toxicity assessments in animals and human trials are also recommended to ascertain its long term safety.